2000
DOI: 10.2166/wst.2000.0066
|View full text |Cite
|
Sign up to set email alerts
|

Increase of anaerobic degradation of particulate organic matter in full-scale biogas plants by mechanical maceration

Abstract: Different concepts of implementation of mechanical pretreatment for enhancing the biogas potential from fibers in manure feedstock were evaluated by sampling before and after macerators at different biogas plants and from a fiber separation unit. An increase of the biogas potential of up to 25% by pretreatment of the whole feed in the macerator before the reactor was observed. Implementation concepts with a treatment of the fibers alone after separation from the manure showed to be not efficient due to a low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(61 citation statements)
references
References 8 publications
2
57
0
2
Order By: Relevance
“…However, a number of studies have investigated pretreatment methods that specifically aim to increase the methane yield of recalcitrant biomass. Size reduction (maceration) of manure fibers led to an increase of 25% [5]. Also, 23% and 30% improvement was achieved with chemical and biological treatment of manure, respectively .…”
Section: Introductionmentioning
confidence: 96%
“…However, a number of studies have investigated pretreatment methods that specifically aim to increase the methane yield of recalcitrant biomass. Size reduction (maceration) of manure fibers led to an increase of 25% [5]. Also, 23% and 30% improvement was achieved with chemical and biological treatment of manure, respectively .…”
Section: Introductionmentioning
confidence: 96%
“…Hartmann et al [21] tested the mechanical maceration of manure and found a 25 % increase on biogas production while the resulted increase was insignificant when only raw manure fibers were treated. Raphique et al [22] tested a thermal, a thermochemical and a chemical [with Ca(OH) 2 )] pretreatment of raw manure fibers and reported a 28 %, a 72 % and a negative increase of CH 4 yield respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hartmann et al (2000), discovered that while steeping the feedstocks, shearing effect played crucial role in increasing the gas production to the cutting of substrate fiber. In another reported study, the cell structure of the substrate was interrupted by sonication (Elliott and Mahmood, 2007).…”
Section: Mechanical Treatmentmentioning
confidence: 99%